The Silviculture and Management of Tropical Rain-forests in India - Stracey, P. D. (Indian Forester, 1959)
The physical features and specific characteristics of the evergreen forests of India are described. The lines along which the silviculture and management of these forests have developed are recounted and caution is advocated in any efforts at intensive working of these forests or at excessive favouring of selected species.